Manual metodológico para la recolección de información - Chaves Barboza, Eduardo (2009)
The manual describes three research techniques (participant observation, focal interview, depth interview), including some methodological suggestions for implementation. The document also explains the categories will be investigated with these techniques, within the research Project “La enseñanza de las Matemáticas en la secundaria costarricense: entre la realidad y la utopía” of the Escuela de Matemática of the Universidad Nacional in Costa Rica. It also details the moments to gather information, the components of the instruments and how to integrate the report of implementation. Finally, the tools are attached in annexes.